CLASSIFICATION OF THE VARIATION OF DESIGN AND DECORATIVE ELEMENTS OF THE FIELD COATS FOR MILITARY AVIATION PILOTS - Рубанка, А. І.; Токар, Г. М.; Стельмах, М. Д.; Семененко, В. В.; Северіна, Є. А. (Art and Design, 2019)
To analyze and to systematize the varieties of design solutions for individual design and decorative elements and units during the manufacturing of the protective field coats for military aviation pilots. The system and structural analysis of the components of the protective field coats for pilots is used; the activity of military personnel is theoretically analyzed and estimated. In order to develop the most effective protective clothes with the improvement of the product functionality, a series of sketches with the varieties of design and decorative elements at the different parts of the product are prepared using the principles of transformation, which will significantly increase the operational capabilities of the protective clothes and meet the demands of the modern consumer. The silhouette of the product and its length, its structural parts, the cut of the sleeve, and the design of the neck line, as well as the varieties of the appliques, pockets and fasteners outside of the area of their placement are studied in detail. On the basis of theoretical researches, an assortment range of the new models of field coats for military aviation pilots is developed taking into account the peculiarities of their professional and qualification duties. Scientific novelty. On the basis of theoretical studies of existing varieties of the protective clothes, an information base of the constitutive elements of the field coats for military aviation pilots is formed for the purpose of their reasonable choice. Practical significance. The most rational design and technology solutions for the constitutive elements – details and units are systematized, depending on the functionality of the product and its operating conditions. Based on the study of the working conditions and the analysis of the world analogues of the field coats for pilots, new design and technology solutions with the improved indicators of ergonomics and aesthetics are developed.